Advances in Cryopreservation of Bull Sperm - Ugur, Muhammet Rasit; Saber Abdelrahman, Amal; Evans, Holly C.; Gilmore, Alicia A.; Hitit, Mustafa; Arifiantini, Raden Iis; Purwantara, Bambang; Kaya, Abdullah; Memili, Erdogan (Frontiers in Veterinary Science, 2019)
Cryopreservation of semen and artificial insemination have an important, positive impact on cattle production and product quality. Through the use of cryopreserved semen and artificial insemination, sperm from the best breeding bulls can be used to inseminate thousands of cows around the world. Although cryopreservation of bull sperm has advanced beyond that of other species, there are still major gaps in the knowledge and technology bases. Post-thaw viability of sperm is still low and differs significantly among the breeding bulls. These weaknesses are important because they are preventing advances both in fundamental science of mammalian gametes and reproductive biotechnology. Various extenders have been developed and supplemented with chemicals to reduce cryodamage or oxidative stress with varying levels of success. More detailed insights on sperm morphology and function have been uncovered through application of advanced tools in modern molecular and cell biology. This article provides a concise review of progress in the cryopreservation of bull sperm, advances in extender development, and frontiers using diverse techniques of the study of sperm viability. This scientific resource is important in animal biotechnology because with the advances in discovery of sperm fertility markers, there is an urgent need to improve post-thaw viability and fertility of sperm through enhanced cryopreservation for precision agriculture to produce food animals to ensure food security on the global scale.